2017
DOI: 10.1007/s00294-017-0767-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron toxicity in yeast: transcriptional regulation of the vacuolar iron importer Ccc1

Abstract: All eukaryotes require the transition metal, iron, a redox active element that is an essential cofactor in many metabolic pathways, as well as an oxygen carrier. Iron can also react to generate oxygen radicals such as hydroxyl radicals and superoxide anions, which are highly toxic to cells. Therefore, organisms have developed intricate mechanisms to acquire iron as well as to protect themselves from the toxic effects of excess iron. In fungi and plants, iron is stored in the vacuole as a protective mechanism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Interference of vacuolar transport encoding gene CCC1 [91,92] Inability to acquire iron [60,93] Manganese Down-regulation of HTB2, HTA1, HTA1, HTBI, HHF [94,95] potentially associated to reduced functioning of manganese peroxidase [96][97][98] Silver Interference in ergosterol biosynthesis [80,99,100] --…”
Section: Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…Interference of vacuolar transport encoding gene CCC1 [91,92] Inability to acquire iron [60,93] Manganese Down-regulation of HTB2, HTA1, HTA1, HTBI, HHF [94,95] potentially associated to reduced functioning of manganese peroxidase [96][97][98] Silver Interference in ergosterol biosynthesis [80,99,100] --…”
Section: Ironmentioning
confidence: 99%
“…Results indicated that, during corneal fungal infection, these fungi acquired iron through siderophores and that the iron-binding agent blocked the ability of the pathogen to acquire siderophore-bound iron, highlighting the inability of the fungi to proliferate without access to iron [93]. In S. cerevisiae, iron toxicity is related to the ability of the cell to transport cytosolic iron to the vacuole via Ccc1 [91,248]. Lin et al showed that ccc1∆ mutants could not transfer cytosolic iron to the vacuole under anaerobic conditions, even with the overexpression of iron mitochondrial transporter Mrs3, effectively inducing toxicity [248].…”
Section: Iron Toxicitymentioning
confidence: 99%
“…The yeast iron detoxification response is mostly triggered by the transcriptional activator protein of the Yap family, Yap5 [reviewed in Li and Ward (2018) ; Rodrigues-Pousada et al (2019) ]. Yap5 associates to Yap response elements (YREs) within the promoter of its target genes independently of iron levels, but only activates transcription when it associates to two [2Fe–2S] clusters through conserved cysteine-rich domains in a mitochondrial ISC-dependent but Grx3/4-independent manner ( Li et al, 2008 , 2012 ; Rietzschel et al, 2015 ).…”
Section: Regulation In Response To Iron Excessmentioning
confidence: 99%
“…Consistent with its crucial function in cytosolic iron detoxification, the expression of CCC1 is finely regulated by iron. In response to iron excess, S. cerevisiae Yap5, a member of the yeast activator protein (Yap) subfamily of transcriptional factors (reviewed in [53] ), activates the expression of CCC1 ( [54] ; reviewed in [55] ) ( Fig. 4 ).…”
Section: Regulation Of Yeast Ccc1 Expression By Irmentioning
confidence: 99%